Candida auris-associated hospitalizations and outbreaks, China, 2018–2023 - Jian Bing; Han Du; Penghao Guo; Tianren Hu; Meng Xiao; Sha Lu; Clarissa J. Nobile; Haiqing Chu; Guanghua Huang (Emerging Microbes and Infections)
The emerging human fungal pathogen Candida auris has become a serious threat to public health. This pathogen has spread to 10 provinces in China as of December 2023. Here we describe 312 C. auris-associated hospitalizations and 4 outbreaks in healthcare settings in China from 2018 to 2023. Three genetic clades of C. auris have been identified during this period. Molecular epidemiological analyses indicate that C. auris has been introduced and local transmission has occurred in multiple instances in China. Most C. auris isolated from China (98.7%) exhibited resistance to fluconazole, while only a small subset of strains were resistant to amphotericin B (4.2%) and caspofungin (2.2%).